The Application of Hamid Shirvani's Design Elements in Urban Spaces of Bende Subdistrict, Kendari City - Nurbaity, Dian Puteri; Akbar, Ibrahim; Firmansyah, Firmansyah; Yuswandi, Yuswandi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Bende Subdistrict is designated for city/government service centers, high-density residential areas, tourism/entertainment zones, and commercial and service areas in Kendari City, Southeast Sulawesi. Its central location has led to uncontrolled development within the area. Given its potential, better management can maximize the area's functions. This study employs a descriptive qualitative method, incorporating the collection of primary and secondary data. The results indicate a lack of order in urban infrastructure management from the perspective of urban design elements. Therefore, this study aims to provide guidance for the government and other stakeholders in developing Bende Subdistrict into a sustainable area.